Lupus Cerebritis as the Initial Presentation of Systemic Lupus Erythematosus in a Young Female - Gosal, Kiranpreet (Cureus, 2021)
The psychiatric and neurological symptoms of systemic lupus erythematosus (SLE) are referred to as lupus cerebritis. The wide range of symptoms associated with SLE can pose a diagnostic challenge. We present a case of lupus cerebritis in a 31-year-old female presenting with psychosis. We present this case to increase awareness of the psychiatric manifestations of SLE that can be mistaken for more common etiologies of psychosis.